Anaerobic Metabolism of Indoleacetate - Ebenau-Jehle, Christa (American Society for Microbiology, 2012)
The anaerobic metabolism of indoleacetate (indole-3-acetic acid [IAA]) in the denitrifying betaproteobacterium Azoarcus evansii was studied. The strain oxidized IAA completely and grew with a generation time of 10 h. Enzyme activities that transformed IAA were present in the soluble cell fraction of IAA-grown cells but were 10-fold downregulated in cells grown on 2-aminobenzoate or benzoate. The transformation of IAA did not require molecular oxygen but required electron acceptors like NAD(+) or artificial dyes. The first products identified were the enol and keto forms of 2-oxo-IAA. Later, polar products were observed, which could not yet be identified. The first steps likely consist of the anaerobic hydroxylation of the N-heterocyclic pyrrole ring to the enol form of 2-oxo-IAA, which is catalyzed by a molybdenum cofactor-containing dehydrogenase. This step is probably followed by the hydrolytic ring opening of the keto form, which is catalyzed by a hydantoinase-like enzyme. A comparison of the proteome of IAA- and benzoate-grown cells identified IAA-induced proteins. Owing to the high similarity of A. evansii with strain EbN1, whose genome is known, we identified a cluster of 14 genes that code for IAA-induced proteins involved in the early steps of IAA metabolism. These genes include a molybdenum cofactor-dependent dehydrogenase of the xanthine oxidase/aldehyde dehydrogenase family, a hydantoinase, a coenzyme A (CoA) ligase, a CoA transferase, a coenzyme B(12)-dependent mutase, an acyl-CoA dehydrogenase, a fusion protein of an enoyl-CoA hydratase and a 3-hydroxyacyl-CoA dehydrogenase, a beta-ketothiolase, and a periplasmic substrate binding protein for ABC transport as well as a transcriptional regulator of the GntR family. Five predicted enzymes form or act on CoA thioesters, indicating that soon after the initial oxidation of IAA and possibly ring opening, CoA thioesters are formed, and the carbon skeleton is rearranged, followed by a CoA-dependent thiolytic release of another CoA thioester. We propose a scheme of an anaerobic IAA metabolic pathway that ultimately leads to 2-aminobenzoyl-CoA or benzoyl-CoA.